2018
DOI: 10.3920/wmj2017.2175
|View full text |Cite
|
Sign up to set email alerts
|

An HPLC-FLD method to measure ochratoxin A in teff (Eragrostis tef) and wheat (Triticum spp.) destined for the local Ethiopian market

Abstract: Wheat (Triticum spp.) is among the top cereal grains in terms of production and consumption in Ethiopia. It can be typically infected with ochratoxin A (OTA) producing fungi both in the field and during storage resulting in animal and human health problems. While there is a wealth of information on the presence of OTA in wheat, the incidence of OTA in teff (Eragrostis tef), a cereal grain produced and consumed traditionally in Ethiopia and Eretria, remains insufficient. The purpose of this study was to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Ayalew et al [ 64 ] found that 24% and 27.3% of cereals and teff samples were positive for OTA (2.7–2106 µg/kg), respectively. Another study by Geremew et al [ 57 ] reported the presence of OTA in 20% of teff flour collected from Addis Ababa. These results indicate that OTA contamination is a serious health concern for Ethiopia because injera (flat bread made out of teff) is a daily meal for majority of people in Ethiopia.…”
Section: Occurrence Of Mycotoxigenic Fungi and Their Toxins In Ethmentioning
confidence: 99%
“…Ayalew et al [ 64 ] found that 24% and 27.3% of cereals and teff samples were positive for OTA (2.7–2106 µg/kg), respectively. Another study by Geremew et al [ 57 ] reported the presence of OTA in 20% of teff flour collected from Addis Ababa. These results indicate that OTA contamination is a serious health concern for Ethiopia because injera (flat bread made out of teff) is a daily meal for majority of people in Ethiopia.…”
Section: Occurrence Of Mycotoxigenic Fungi and Their Toxins In Ethmentioning
confidence: 99%
“…While generally there are a lot of data about ochratoxin A in wheat, this information is rather scarce for Ethiopia and hardly exists for Ethiopian teff. Therefore, Geremew et al (2018) developed an analytical method to determine ochratoxin A in wheat and teff. The method was based on alkaline extraction, solid-phase extraction clean-up and HPLC with fluorescence detection.…”
Section: Foreword Wmj Special Issue 'Mycotoxins In Africa'mentioning
confidence: 99%